Numerical simulation on the thermal performance of a PCM-containing ventilation system with a continuous change in inlet air temperature. (January 2020) - Sun, Wanchun; Huang, Rui; Ling, Ziye; Fang, Xiaoming; Zhang, Zhengguo
Abstract: Herein a numerical study was conducted on a ventilation system integrated with the inorganic PCM panels having enhanced thermal conductivity. The overall thermal performance of the ventilation system was improved by adjusting the inlet condition and the thermal properties of the PCM. With the temperature of the inlet air fluctuating from 17.4 to 33.1 °C, the effects of the inlet air flow rate and the thickness and thermal conductivity of the panels were investigated, aiming at making the outlet air temperature closer to the thermal comfort range. It was showed that the outlet temperature fluctuation reduced as the inlet air flow rate decreased or the thickness of the panels increased. Moreover, a PCM utilization rate was introduced to evaluate the PCM performance during the melting-solidification process. It was found that narrowing the phase change temperature range of the PCM in the outlet channel could further reduce the maximum outlet temperature and improve the PCM utilization rate. In addition, when the inlet air flow rate was 11.47 kg/h and the thickness of the PCM panels was 12 mm, the ventilation system with the panels having a thermal conductivity of 13.0 W/(m·K) exhibited the smallest outlet temperature fluctuation of 22.5–27.9 °C. Highlights: A numerical model of the PCM-containing ventilation system is constructed. The effects of air velocity, PCM amount and thermal conductivity of PCM are explored. Properly increasing the PCM amount can reduce air temperature fluctuation. Reducing the phase change temperature range can improve the utilization of PCM. The thermal conductivity of the PCM has an optimum value.